The Influence of Academic Supervision, Work Motivation, and Collaborative Learning Practices on Teacher Performance in Junior High Schools in Berau Regency - Sitorus, Ellen Rotua Basaria; Azainil; Nurlaili (Borneo Educational Journal (Borju), 2025)
Academic supervision, work motivation, and collaborative learning practices are key aspects influencing teacher performance. These three elements support the creation of a higher quality and more effective educational environment. This study aims to assess the impact of academic supervision, work motivation, and collaborative learning practices on teacher performance at public junior high schools in Berau Regency. Utilizing a quantitative approach with cluster random sampling, the research population consists of 20 accredited A public junior high schools totaling 507 teachers, while the sample includes 9 accredited A schools with 244 teachers. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression. The findings reveal that academic supervision significantly impacts teacher performance with a contribution of 35%. Additionally, work motivation has a smaller effect at 6.9%, while collaborative learning practices also contribute 35%. Collectively, these factors account for 35% of teacher performance, with the remaining influence attributed to unidentified factors. The study emphasizes the importance of synergy between academic supervision providing constructive feedback, relevant incentives to motivate teachers, and developing learning communities that support ongoing professional growth. School leaders should enhance academic supervision through targeted training, local governments should offer more effective performance-based rewards, and schools should facilitate sustainable learning community programs to foster continuous innovation in teaching and improve teacher performance consistently. This research is expected to serve as a reference for educational policy in Berau Regency and enhance the overall quality of education in Indonesia